2012
DOI: 10.1038/srep00707
|View full text |Cite
|
Sign up to set email alerts
|

Direct Optical Characterization of Graphene Growth and Domains on Growth Substrates

Abstract: We detailed a facile detection technique to optically characterize graphene growth and domains directly on growth substrates through a simple thermal annealing process. It was found that thermal annealing transformed the naked Cu to Cu oxides while keeping graphene and graphene-covered Cu intact. This increases the interference color contrast between Cu oxides and Cu, thus making graphene easily visible under an optical microscope. By using this simple method, we studied the factors that affect graphene nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
125
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 42 publications
7
125
0
Order By: Relevance
“…As shown in Fig. 1A, optical microscope (OM) image clearly shows HGG after oxidizing the underlying Cu strip at 160°C for 6 min [27]. The average length of HGG was about 25 lm.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Fig. 1A, optical microscope (OM) image clearly shows HGG after oxidizing the underlying Cu strip at 160°C for 6 min [27]. The average length of HGG was about 25 lm.…”
Section: Resultsmentioning
confidence: 97%
“…2. In order to visualize the graphene layer, the graphene-grown copper sample was optionally oxidized at $165°C for 6 min on a hot plate in an ambient atmosphere [27].…”
Section: Cvd Growth Of Graphenementioning
confidence: 99%
“…In order to verify complete coverage of graphene, Cu samples were heated at 180°C in ambient conditions for 30 min. Graphene, which acts as a passivation barrier, prevents the oxidation of Cu [24] (see Supporting Information for full description of heating test and XPS studies). The heating test was performed on all Cu samples and it was found that even 5 min of growth prevents Cu oxidation, indicating complete coverage of graphene on Cu.…”
Section: Graphene Growth On Copper Filmsmentioning
confidence: 99%
“…For example, Kim et al developed a simple method to visualize graphene grains and GBs by imaging the birefringence of a graphene surface covered with nematic liquid crystals, taking advantage of the orientation of the liquid crystals with the underlying graphene lattice (thus mapping the graphene grains and GBs to those of the corresponding liquid crystal domains) 96 . Using optical microscopy, one can also enhance the contrast of grains and make GBs more visible by taking advantage of the more effective oxidation of substrate (Cu) in the region exposed or under GBs (which can be further functionalized to facilitate oxidation) 97,98 . Similar techniques can also be used to facilitate AFM and other types of GB imaging 99 .…”
Section: Optical Imaging and Characterizationmentioning
confidence: 99%